(untitled) - French, Wendell L. (Englewood Cliffs, NJ, 1995)
French and Bell explore the improvement of organizations through planned, systematic, long-range efforts focused on the organization's culture and its human and social processes. They present a concise but comprehensive exposition of the theory, practice and research related to organization development. The Fifth Edition reflects recent developments, advances and expansions, and research.
Keywords: Organizational change,Thay đổi tổ chức